Pengaruh Work Load dan Job Dissatisfaction terhadap Loyalitas Kerja Karyawan - Fitri Novianti; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
Abstract. Competition in the industrial world triggers the company’s efforts to create a strategy of increasing the commitment and loyaly of its emplooyees. Loyalty becomes an important foundation for companies achieve common goals. Therefore, companies must have qualified human resources to be willing to be commited and loyal to work. This study aims to determine whether there is an influence between wook load an job dissatisfaction on employee work loyalty. Research focus in this research are employees of the production dvision. This research uses descriptive and verifiable methods, using a quantitative research approach and operating the calculations using the IBMSPSS 25.0 program. Collection of data obtained through questionnaires, observations, interviews and some analytical calculations. The sampling technique is saturated sampling. The respondents in this study were employees of the production division of PT. Pindad Enjiniring which totaled 53 people. The result of the study concluded that: 1) work load (X1) partially affects Employee Work Loyalty (Y). 2) Job Dissatisfaction (X2) partially has a significant effect on Employee Work Loyalty (Y). 3) Work Load (X1) and Job Dissatisfaction (X2) simultaneously have a significant effect on Employee Work Loyalty (Y). Abstrak. Persaingan dalam dunia industry memicu upaya perusahaan untuk menciptakan strategi peningkatan komitmen dan loyalitas para karyawannya. Loyalitas menjadi landasan penting bagi perusahaan untuk mencapai tujuan bersama. Oleh karena itu perusahan harus memiliki SDM yang memumpuni untuk bersedia komitmen dal loyal dalam bekerja. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh antara work load dan job dissatisfaction terhadap loyalitas kerja karyawan. Research focus pada penelitian ini adalah deskriptif dan verifikatif, dengan menggunakan pendekatan kuantitatif dan mengoprasikan perhitungannya menggunakan program IBMSPSS 25.0. pengumpulan data yang diperoleh melalui kuesioner, observasi, wawancara, dan beberapa perhitungan analisis. Teknik penarikan sampel adalah sampling jenuh. Responden dalam penelitian ini adalah karyawan divisi produksi PT. Pindad Enjiniring yang berjumlah 53 orang. Hasil penelitian ini menyimpulkan bahwa: 1) work load (X1) secara parsial berpengaruh signifikan terhadap loyalitas kerja karyawan (Y). 2) job dissatisfaction (X2) secara parsial berpengaruh signifikan terhadap loyalitas kerja karyawan (Y). 3) work load (X1) dan job dissatisfaction (X2) terhadap loyalitas kerja karyawan (Y).